The characteristics of benign prostatic hyperplasia (BPH) in Rumah Sakit Haji Medan - D.dr Shahrul Rahman, Sp.PD., Finasim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Benign prostatic hyperplasia (BPH) is an enlarged prostate glan caused by progressive hyperplasia of glandular cells or stoma cells from prostate tissues. BPH is a common problem that increases in people from 40 years old. The symptom is lower urinary track symptoms (LUTS) that consist aims to know the characteristic of BPH patients in RSU Haji Medan from January to December 2015. Research design of this study is descriptive studies. The population of the study consist of patients who were diagnosed with BPH in RSU Haji Medan from January to December 2015. Total smapling method was used. Research data were retrieved by taking the patients' entire medical record with BPH in RSU Haji Medan from January to December 2015.